Konstruksi Identitas Gender pada Remaja Pengguna Media Sosial Twitter - Kamisya, Annisa Nur; Setiawan, Rizki (EDU SOCIATA ( JURNAL PENDIDIKAN SOSIOLOGI ), 2024)
This study explores the socio-cultural dynamics undergirding the formation of adolescent gender identities through their engagement with the social media platform Twitter. Employing a virtual ethnographic methodology, the research analyzes how adolescents leverage Twitter’s affordances such as bios, tweets, and shared content to construct and performatively present gendered identities aligned with social norms. The findings indicate female adolescents tend to utilize language and symbolic representations associated with femininities, while male adolescents gravitate towards masculinity-connoting elements. However, gender identity construction on Twitter is revealed to be a fluid process shaped by intersecting factors including age, cultural milieu, and individualized experiences. The study elucidates some adolescents’ attempts to negotiate and subvert hegemonic gender stereotypes, such as females engaging in masculinized hobbies or males embracing feminized interests. Nonetheless, such transgressions frequently encounter negative social repercussions and marginalization. Conversely, social media simultaneously facilitates discourse around more inclusionary gender identities and the celebration of diverse gender expressions.